What is the learning effect of video review in postgraduate medical education: a systematic review - Marieke Robbrecht; Myriam Van Winckel; Antonius Mulder; Mieke Embo (BMC Medical Education)
Abstract Background Video review is a feasible, commonly used learning tool, but current literature lacks a comprehensive review of its impact on learning in postgraduate medical education. This systematic review aims at examining the learning effect of video review of resident performance in clinical practice during postgraduate medical education. Methods A systematic literature search was conducted from May 2023 to July 2023 with an update on 12/12/2023. Databases of MEDLINE (Pubmed), Web of Science, Embase and ERIC (through Webquest) were searched. Eligible articles had to describe the learning effects of video review in clinical practice in postgraduate medical education. The videos had to be actively recorded in a setting where a camera was not normally used for standard patient care. The investigated effect needed to be classified at least as a Kirkpatrick level 2. We iteratively developed a standardized data extraction form to extract study characteristics. The methodological quality of the individual studies was assessed using the Medical Education Research Quality Instrument. Results Out of 9323 records after deduplication, 11 studies were included. The designs were randomised controlled trials (n = 4) and single-group pre-test post-tests trials (n = 7). The studies had outcomes related to knowledge and skills (n = 5), resident behaviours (n = 5) and patient outcome (n = 1). All studies reported outcomes regarding learning effect. Conclusions Video review appears to have a positive impact on residents’ learning outcomes in postgraduate medical education. However, it is mostly not tailored to the specific learning needs of residents, and there is a lack of information regarding its optimal integration with other learning methods and within distinct clinical contexts. The heterogeneity observed among the included studies makes it challenging to formulate clear recommendations in the use of video.